Статистичні оцінки живучості гребель - Стефанишин, Д.В. (Екологічна безпека та природокористування, 2012)
The vitality assessment of dams on the statistical analysis of accident rate has been realized. The vitality statistical values of dams may be used for grounding of dam safety depending on type and construction mode of structures.